Mobile hospitals routing for prioritized patients - Tarhini, Abbas (2017)
Health is an essential factor for sustaining a better life in a better world. Today, for different reasons, several districts in our countries would be deprived from the needed health support and thus, in such cases, we need to deliver health care to those regions. Despite of its high cost, mobile hospital remains one of the good solutions to deliver health care to critical areas in our countries. A recognized problem in this domain is minimizing the cost of mobile hospitals rout in a way that the number of served patients is maximized. This problem is known as the mobile hospitals routing problem (MHRP). The purpose of this paper is to present a novel approach that, within the given limited resources, it minimizes the cost and the traveling distance of mobile hospitals while maximizing the number of patients served as per priorities assigned according to the patients’ medical status. A lot of research has been conducted regarding this topic; still, up to our knowledge, none used an intelligent variable neighbourhood search approach. This paper implements and tests an intelligent variable neighbourhood search algorithm for MHRP. The results show that our proposed method is reliable and efficient in terms of solution quality and time.